Ensuring of financial sustainability of railway transport in Ukraine - Kravchenko, O.O. (Економіка промисловості, 2014)
The article shows the important role of railway transport in the Ukrainian economy. Difficulties in the process of reforming the industry and the economic crisis in Ukraine determine deterioration in the financial condition of the railway transport. This reflects negatively on the ability to carry cargo and passengers with the necessary quality and speed. Therefore the aim of the article is to study the features of the financial condition of railway transport of Ukraine and the formation of the system of constraints to maintain its financial stability in unsteady conditions of the institutional environment. The article stipulates that used indicators describing the financial condition of the enterprises do not consider the particular characteristics of the plant and the financial and economic activities of a particular object, which leads to incorrect test results. Investigated the financial condition of the railway transport of Ukraine. It is shown that in order to prevent further accumulation of negative trends in operating and financial sector there is an objective need for the formation of severe restrictions managing its financial assets to improve their effectiveness in the short and long term. The article suggested and justified system of constraints, which includes 1) a primary funding operations, and 2) the volume balance of positive andnegative cash flows, and 3) synchronization generating operational, financial and investment cash flow, and 4) maintaining an optimum balance of funds as reserves to ensure financial sustainability 5) providing liquidity cash flow. Implementation of the proposed system of constraints will contribute to a) improve the operational management of cash flows from a position of balance of income and expenditure of funds, and b) increase the liquidity of the balance of the industry, and c) increase the investment attractiveness of the railway transport of Ukraine, and d) the release of funds from the operational turnover for capital investment in the development of the industry. Improving the management of the financial condition and financial sustainability of railway transport should also include 1) reduction in line with the current regulatory framework, and 2) the development of methodology for assessing the financial condition of the provisions and financial stability, and 3) implementation of the necessary changes in the organization of financial work of railway transport; 4) the full implementation of the system of financial planning, and 5) development of monitoring operational and financial performance.